Bipolar Neutrosophic Graph Structures - Akram, Muhammad; Sitara, Muzzamal (Journal of the Indonesian Mathematical Society, 2017)
In this research study, we introduce the concept of bipolar single-valued neutrosophic graph structures.We discuss certain notions of bipolar single-valued neutrosophic graph structures with examples.We present some methods of construction of bipolar single-valued neutrosophic graph structures.We also investigate some of their prosperities.